Lecturer â€œAleksander Xhuvaniâ€ State University - Hurmi, Bahar Turhan (Richtmann Publishing, 2012)
Following the September 11, 2001 terrorist attacks on the United States, the Europan Union has acted on several fronts toreinforce its existing and nascent capabilities to combat terrorism. The European Concil adopted a comprehensive Plan of Action andreached politicaagreement on a number of important counterterrorism initiatives. This paper provides a critical analysis of all thesemeasures and reveals that the EU’s counterterrorism policy is more of a paper tiger than it is an effective counterterrorism device. Thefirst part provides a brief historical overview, which analyses the event-driven and contingent development of the EU’s counterterrorismpolicy. The second part presents a critical assessment of policy outcomes according to the objectives set out in the EU’sCounterterrorism Strategy. Measures ‘to pursue’, and ‘to protect’ against terrorists seem to have grown substantially. In practice,however, they are undercut by a lack of focus and use at the operational level. Similarly, EU’s capacities ‘to respond’ to terrorism havebeen boosted, but there are doubts as to their relevance in real crisis situations. Yet most importantly, the EU remains unable to do more‘to prevent’ terrorism. This seriously limits the overall effectiveness and output legitimacy of the EU’s efforts. The concluding third partassesses these findings and argues that EU counterterrorism policy is ineffective and there is an immediate need for more cooperativepolicies and implementations.